急性大血管闭塞性卒中机械取栓术后出血转化的研究进展 Clinical Advances in Hemorrhagic Transformation after Mechanical Thrombectomy for Acute Ischemic Stroke due to Large Vessel Occlusion - KANG Zhiming, MEI Bin (Zhongguo cuzhong zazhi, 2024)
机械取栓是发病24 h内的急性前循环大血管闭塞性缺血性卒中的标准治疗，出血转化是其最常见、最严重的并发症，不仅会延长患者的住院时间，而且会导致预后不良，抵消机械取栓带来的获益。因此，有必要科学地认识这一并发症。近年来，国内外学者围绕机械取栓术后出血转化开展了广泛研究，本文结合国内外文献，从出血转化的定义、分型、发生率、危险因素、预防和管理等方面进行综述。 Abstract: Mechanical thrombectomy is the standard treatment for acute ischemic stroke due to large vessel occlusion in the anterior circulation within 24 hours of onset, and hemorrhagic transformation is the most common and serious complication, which not only increases the length of hospital stay, but also leads to a poor prognosis and negates the benefits of mechanical thrombectomy. Therefore, it is of great importance to scientifically understand this complication. Recently, domestic and foreign scholars have carried out extensive investigations on the hemorrhagic transformation after mechanical thrombectomy. In this paper, the definition, classification, incidence, risk factors, prevention and management of hemorrhagic transformation were reviewed based on domestic and foreign literatures.